Penegakan Hukum terhadap Pembuangan Limbah Cair oleh Usaha Garmen di Kabupaten Gianyar - Gede Krisna Adi Putra; I Putu Gede Seputra; Luh Putu Suryani (Warmadewa Press, 2020)
Gianyar Regency is one of the districts in Bali which is a favorite of tourists. Many of these tourists are interested in local garment products, so many small garment industries are developing. However, of the many garment industries there are still many who are less concerned with disposing of the liquid waste produced by the garment without processing it first to make it more eco-friendly. Based on this background, this research was conducted with the aim of describing how to monitor the disposal of liquid waste by garment businesses in Gianyar Regency and what are the obstacles to law enforcement against garment businesses that dispose of liquid waste in Gianyar Regency. This research was designed using the empirical legal method. This research was conducted in Gianyar Regency. The results of this study indicated that the supervision of liquid waste disposal in Gianyar Regency was carried out by the Environmental Service Office of Gianyar Regency by checking the documents owned by the garment business owner. Then, they compiled a monitoring report based on facts and field findings. Finally, the Gianyar Regency Environmental Service made recommendations and submitted recommendations on the results of the supervision. The barriers to law enforcement against garment businesses that dispose of liquid waste in Gianyar Regency are legal facilities, law enforcement officers, facilities and facilities, permits, public legal awareness.